Environmental Leadership Character Based on the Local Wisdom of Horticultural Agriculture in Ngada Flores - Labu, Norbertus; Widianarko, Y. Budi; Utami, Margaretha Sih Setija (Soegijapranata Catholic University, 2023)
The Ngada Regency Government is developing horticulture using a group approach, namely farmer groups. Each farmer group is led by a group leader. The farmer group leader applies an environmental leadership approach based on local wisdom in developing horticultural agriculture. One of the factors that determines the success or failure of an environmental leader is leadership character. For this reason, it is necessary to identify and explain the character of environmental leadership based on local wisdom. This research aims to determine and describe the character of environmental leadership based on local wisdom in the development of horticultural agriculture. This research is qualitative research using hermeneutic analysis techniques. Data collection was carried out through observations of groups of horticultural farmers in Ngada Regency, in-depth interviews with two expert sources and 6 (six) heads of farmer groups, as well as focus group discussions (FGD) with 24 members of farmer groups. The research results show that the character of environmental leadership based on local wisdom in the development of horticultural agriculture is the character of hard work, moral character and spiritual character. This research contributes on-site knowledge-based environmental leadership.